Utilization of Organic Fertilizer in Ghana: Implications for Crop Performance and Commercialization - John K. Bidzakin; Anil Graves; Dadson Awunyo-Vitor; Osei Yeboah; Iddrisu Yahaya; Esther Wahaga (Advances in Agriculture)
Organic fertilizer commercialization may present a great opportunity to help deal with the issue of solid waste management and help improve the declining soil problems in many developing countries. Ghana’s solid waste is predominantly organic, which is suitable for organic fertilizer production. This paper seeks to establish relationship between organic fertilizer usage and crop farm performance and assess its commercialization potential. The study employed a farmer-survey and key informant interviews to generate data from 300 farmers randomly selected across three regions in Ghana. The computed organic fertilizer use rate is 42% among farmers surveyed, and organic fertilizer is primarily used in vegetable and maize production. The estimated current demand for organic fertilizer is about 0.7 million t/annum with a potential to rise to about 2.7 million t/annum in the long term. This will however require sensitization on its importance, availability, and affordability. The study has established a strong relationship between organic fertilizer adoption and farm performance increasing yield by 57%, income by 53%, and gross margins by 63%. There is obviously a cost reduction when organic fertilizer is adopted. Organic fertilizer adoption was found to be mainly related to farmer base organization membership status, access to extension services, access to organic fertilizer, and transport cost. Organic fertilizer commercialization has the potential to make Ghana a net exporter of fertilizer and create sustainable jobs for the youth. We recommend the use of organic fertilizer by farmers and highly recommend the commercial production of organic fertilizer.